Disaster Preparedness Design in Secondary School Environment - Kamaruddin, Syamsu A (JUPE : Jurnal Pendidikan Mandala, 2024)
The design of disaster preparedness in secondary schools emphasizes coordination, information management, the use of early warning systems, and education and training. Preparing schools for disasters is crucial to minimizing risks and safeguarding the the health and welfare of students, teachers, and other members of the school community. This study employs a literature review approach, analyzing existing theories and practices related to disaster preparedness, including inter-agency coordination, disaster information management, and the application of early warning systems suitable for secondary schools. Using a qualitative literature review method, this research examines academic publications, policy reports, and other relevant documents to identify critical aspects of disaster preparedness design for schools. The study involves collecting secondary data from books, scholarly articles, and official records concerning coordination, information management, early warning systems, and training programs. These data are qualitatively analyzed to uncover patterns, strategies, and recommendations for enhancing school disaster preparedness. Findings highlight that effective coordination among schools, government bodies, and related institutions is essential for developing a robust preparedness system. Efficient and timely information management ensures that school communities are well-informed about emergency procedures. Integrated early warning systems, utilizing communication tools and routine drills, significantly enhance awareness and readiness among school members. Additionally, ongoing education and structured training for students, teachers, and staff improve disaster response skills and understanding, ultimately reducing potential losses.